(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
The study aimed to determine the degree of availability of the digital readiness requirements necessary for implementing the digital transformation strategy in Syrian universities. This was pursued through examining six major requirements identified in the relevant literature: administrative and organizational requirements, physical and digital infrastructure requirements, organizational culture requirements, teaching and learning requirements, student experience requirements, and research and innovation requirements. The study adopted the deductive approach as its general methodological framework, while also drawing on the analytical approach. To achieve the study objectives, a questionnaire based on a five-point Likert scale was designed and distributed to a random sample of academic leaders and faculty members at the universities under investigation, thereby enabling an assessment of the state of digital readiness in these higher education institutions. A total of 388 questionnaires were found valid for statistical analysis. The findings indicated that the degree of availability of the digital readiness requirements necessary for implementing the digital transformation strategy in Syrian public and private universities was low overall, with variation across these requirements. Physical and digital infrastructure requirements were available to a very low degree. Administrative and organizational requirements, teaching and learning requirements, and student experience requirements were available to a low degree, whereas organizational culture requirements and research and innovation requirements were available to a moderate degree.